Productivity and economics of transplanted and direct-seeded rice (Oryza sativa) - based cropping systems in Indo-Gangetic Plains - Gangwar, K S; Tomar, O K; Pandey, D K (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted during 2003-05 at Modipuram to assess the effect of rice crop establishment methods of rice (0ryza sativa L.) to improve the productivity and profitability of rice-based cropping systems. Direct-seeded hybrid rice yielded (8.20 tonnes/ha) higher than the manually transplanted (7.65 tonnes/ha). The yields of subsequent crops after aerobic rice (Oryza sativa L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) (5.69 tonnes/ ha), chickpea (Cicer arietinum L.) (2.27 tonnes/ha) and Indian mustard [Brassica juncia (L.) Czernj & Cosson] (1.82 tonnes/ha), which were higher than when taken after transplanted rice with yield of 4.96, 1.63 and 1.42 tonnes/ha for wheat, chickpea and mustard respectively. The system productivity of direct-seeded rice-wheat, direct-seeded rice-chickpea and direct seeded rice-mustard were higher (14.96, 14.48 and 13.41 tonnes/ha respectively) compared with the transplanted rice-based cropping system. The corresponding system productivity (13.53, 12.12 and 11.81 tonnes/ha respectively). Root dry matter was also recovered higher for aerobic rice-based cropping systems compared to that of transplanted rice-based cropping systems. The maximum net retums (Rs 50 405 tonnes/ha) and benefit: cost ratio (1.20 g/30 cm3) was recorded under direct seeded rice than transplanted. After 2 crop cycles, significantly higher infiltration rate (1.32 cm/hr) was recorded under direct seeding (dry bed) conditions while greater values of bulk density (1.49 Mg/cm3), soil organic carbon (0.53%), available P (24.67 kg/ha) and K (172.50 kg/ha) were recorded under mechanical transplanting (puddled). Similarly higher total nutrient uptake (415 kg/ha) was recorded in rice-wheat sequence under mechanical transplanting (puddled).